Analisis Makna Idiom Bahasa Jepang dengan Leksem Gigi (æ¯) - Mariyam Aufira Nabila; Ashlikhatul Fuadah; Dewi Kusmiati; Ittaqillah Haisma Kunta (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2022)
Abstract This study aims to determine the lexical and idiomatic meaning of idioms with tooth lexeme (歯). This research is a qualitative descriptive study with data collection methods used is observation methods and followed by note-taking techniques. The data collected in this study were obtained from dictionaries and websites. The collected data were analyzed using the “padan ekstralingual’ method, namely by describing the lexical and idiomatic meanings of idioms with tooth lexeme (歯). The results of the analysis are presented with an informal presentation method. From the analysis of 11 data, it can be concluded that 1) the tooth lexeme (歯) contains 4 meanings, the meaning of space, the meaning of attitude, the meaning of expression, and the meaning of condition 2) there is a relationship between lexical meaning and idiomatic meaning in idioms with tooth lexeme (歯) 3) the idiomatic meaning of idioms with tooth lexemes (歯) can be traced from its lexical meaning. Future research is expected to be able to examine more deeply the meaning of idioms with tooth lexemes (歯) or examine idioms that use animals, natural conditions, etc. Keywords: Idioms, Japanese linguistic, semantic, tooth lexeme Abstrak Penelitian ini bertujuan untuk mengetahui makna leksikal dan idiomatikal pada idiom dengan leksem gigi (歯). Penelitian ini merupakan penelitian deskriptif kualitatif dengan metode pengumpulan data berupa metode simak dan dilanjutkan dengan teknik catat. Data pada penelitian ini diperoleh melalui kamus dan website. Data yang telah terkumpul dianalisis dengan metode padan ekstralingual, yaitu dengan mendeskripsikan makna leksikal dan idiomatikal idiom dengan leksem gigi (歯). Hasil analisis disajikan dengan metode penyajian informal. Dari hasil analisis 11 data, dapat disimpulkan bahwa 1) leksem gigi (歯) mengandung 4 makna, makna ruang, makna sikap, makna ekspresi, dan makna kondisi 2) terdapat hubungan antara makna leksikal dan makna idiomatikal dalam idiom dengan leksem gigi (歯), 3) makna idiomatikal dari idiom dengan leksem gigi (歯) dapat ditelusuri dari makna leksikalnya. Penelitian selanjutnya diharapkan dapat mengkaji lebih dalam makna idiom dengan leksem gigi (歯) atau mengkaji idiom yang menggunakan hewan, keadaan alam, dan lain sebagainya. Kata Kunci: Idiom, leksem gigi, linguistik bahasa Jepang, semantik